Trees of Panama and Costa Rica - Condit, Richard, 1956- (Princeton field guides., 2011)
This is the first field guide dedicated to the diverse tree species of Panama and Costa Rica. Featuring close to 500 tropical tree species, Trees of Panama and Costa Rica includes superb color photos, abundant color distribution maps, and concise descriptions of key characteristics, making this guide readily accessible to botanists, biologists, and casual nature lovers alike. The invaluable introductory chapters discuss tree diversity in Central America and the basics of tree identification. Family and species accounts are treated alphabetically and describe family size, number of genera and s.